2014
DOI: 10.6026/97320630010052
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Screening of Indonesian Herbal Database as HIV-1 Protease Inhibitor

Abstract: HIV-1 (Human immunodeficiency virus type 1)׳s infection is considered as one of most harmful disease known by human, the survivability rate of the host reduced significantly when it developed into AIDS. HIV drug resistance is one of the main problems of its treatment and several drug designs have been done to find new leads compound as the cure. In this study, in silico virtual screening approach was used to find lead molecules from the library or database of natural compounds as HIV-1 protease inhibitor. Virt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 27 publications
0
7
0
1
Order By: Relevance
“…New HIV‐1 protease inhibitor candidates were recently predicted using virtual screening of plant‐derived small molecule libraries, and amaranthin was listed as the third best of all the candidates (Yanuar et al ., ); however, because this method was not empirically verified, we directly tested whether amaranthin inhibits HIV‐1 protease activity. Amaranthin and betanin were extracted and purified from the transformed BY‐2 cell line and added to a mixture of HIV‐1 protease, and HIV‐1 protease substrate, whose cleavage was monitored by HPLC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…New HIV‐1 protease inhibitor candidates were recently predicted using virtual screening of plant‐derived small molecule libraries, and amaranthin was listed as the third best of all the candidates (Yanuar et al ., ); however, because this method was not empirically verified, we directly tested whether amaranthin inhibits HIV‐1 protease activity. Amaranthin and betanin were extracted and purified from the transformed BY‐2 cell line and added to a mixture of HIV‐1 protease, and HIV‐1 protease substrate, whose cleavage was monitored by HPLC.…”
Section: Resultsmentioning
confidence: 99%
“…These results suggested that the addition of one glucuronic acid moiety is important for HIV-1 protease inhibition. Amaranthin was previously selected as the third most effective potential inhibitor of HIV-1 protease activity through virtual screening of substances that bind to the binding site of saquinavir, an artificial HIV-1 protease inhibitor (Yanuar et al, 2014). This suggests that amaranthin binds to HIV-1 protease and inhibits its function through the same mechanism as saquinavir.…”
Section: Discussionmentioning
confidence: 99%
“…The materials and methods described in this study were modified from the studies by Yanuar et al, Syahdi et al,25,26]. A three-dimensional structure of DNMT1, positive and negative control compounds, and active herbal compounds contained in the HerbalDB were used in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Main antiviral activities References Allium cepa L. Alliaceae* Allium cepa has been patented to be used in HIV/AIDS treatment Yanuar et al (2014) Allium sativum L. Alliaceae* Allicin and other thiosulfinates exhibit activity of the herpes simplex virus type 1 and the para-influenza virus type 3. Webert et al (1992) The garlic extract had inhibitory effects on the coronavirus IBV (Infectious bronchitis virus) in the chickens' embryo Mohajer et al (2016 --…”
Section: Plant Namesmentioning
confidence: 99%